The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jvim.15931
|View full text |Cite
|
Sign up to set email alerts
|

Acute on chronic kidney disease in dogs: Etiology, clinical and clinicopathologic findings, prognostic markers, and survival

Abstract: Background: Chronic kidney disease (CKD) and acute exacerbation of CKD (ACKD) are common in dogs. Objective: To characterize the etiology, clinical and laboratory findings, and shortand long-term prognosis of dogs with ACKD. Animals: One hundred dogs with ACKD. Methods: Medical records of dogs diagnosed with ACKD admitted to a veterinary teaching hospital were retrospectively reviewed. Results: The most common clinical signs included anorexia (84%), lethargy (77%), vomiting (55%) and diarrhea (37%). Presumptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…The ICU is a place to rescue severely ill patients, and most patients suffer from multiple organ failure. It has been reported that the mortality rate of patients with more than 2 failed organs is more than 50%, and that of patients with more than 4 failed organs is 100%, which seriously affects the quality of life and safety of patients[ 3 , 4 ]. Studies have shown that the release of proinflammatory mediators is increased in severely ill patients, and then tissue replacement downregulates the release of proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The ICU is a place to rescue severely ill patients, and most patients suffer from multiple organ failure. It has been reported that the mortality rate of patients with more than 2 failed organs is more than 50%, and that of patients with more than 4 failed organs is 100%, which seriously affects the quality of life and safety of patients[ 3 , 4 ]. Studies have shown that the release of proinflammatory mediators is increased in severely ill patients, and then tissue replacement downregulates the release of proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations or dysfunction of AQP2 and AVPR2 could cause nephrogenic diabetes insipidus (NDI), which disrupted water balance and resulted in the excretion of large amounts of dilute urine [18,19]. Previous research has shown that AQP2 inadequacy can affect water balance in the kidney, which is common in humans and animals such as dogs, rats, mice, horses, and young beef cattle [1,[20][21][22][23]. Furthermore, the structure of the canine kidney is unipyramidal, which differs from that of a human [24].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a typical disease in senior dogs and cats. The estimated CKD incidence in dogs and cats is 0.5-1.5%, with more than 10% of dogs and 30% of cats over the age of 15 being diagnosed with CKD [ 1 , 2 ]. CKD is defined as impairment and irreversible renal dysfunction and/or structure that results in progressive disease [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations